Penguatan Ekowisata Melalui Keterlibatan Masyarakat dan Strategi Keberlanjutan Lingkungan - Dumumpe, Jessica Harry; Pratama, Aditya Putra; Saroinsong, Fabiola Baby; Langi, Martina Agustina (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
Ecotourism is a nature-based form of tourism that focuses on environmental conservation and improving local community welfare. This article highlights the crucial role of communities in developing sustainable ecotourism through a systematic review of publications from 2014–2024. The findings reveal that community involvement plays a strategic role in all stages of ecotourism management—from planning and implementation to evaluation. In rural Indonesia, ecotourism often serves as a primary or supplementary income source, especially for young people, through roles such as tour guides, homestay providers, boat operators, and environmental conservationists. Community participation is reflected through self-initiated actions, village deliberations, the establishment of Tourism Awareness Groups (Pokdarwis), youth enterprises, and local regulations supporting sustainable governance. For instance, the high participation rate in Pemuteran Village (77.67%) demonstrates collective awareness of environmental preservation as a foundation for economic resilience. However, challenges remain, including limited understanding of ecotourism’s economic benefits, inadequate infrastructure (especially homestays and sanitation), and low foreign language proficiency. The study concludes that the success of community-based ecotourism depends on capacity building, inclusive governance, and sufficient infrastructure to promote sustainable development and local environmental conservation.